What Are Leverage, Company Size, and Social Disclosure Considered to Reduce Market Response to Earnings Response Coefficient as an Intervening Variable? - Abd. Rohman Taufiq; Lin Oktris; Maisarah Mohamed Saat (AKRUAL: JURNAL AKUNTANSI, 2024)
Introduction/Main Objectives: This research examined the influence of leverage, company size andsocial disclosure on the earnings response coefficient as an intervening variable. BackgroundProblems: Research showed that leverage ability, company size, and social disclosure influence theearning response coefficient. Furthermore, the company size variable positively influenced ERC invarious industrial sector companies on the Indonesian Stock Exchange. Research Methods: Thistype of research used quantitative methods. The research data was manufacturing companies thatwere registered with an IPO before 2016 and were still listed on the IDX from 2016 to 2020. Forthis reason, this regression model was suitable for testing and examining the effect of leverage onthe earning response coefficient. Finding/Results: The larger the company size increases the marketresponse because the company was considered capable of providing high returns. The socialdisclosure variable does not influence ERC in various industrial sector companies on the IndonesianStock Exchange. Social disclosure was a principle or reaction carried out by companies toparticipate in community activities in general. This practice causes the company's asset value andprofits low while the debt value and losses were high. Conclusion: High social disclosure wasconsidered to reduce market response. On the other hand, low social disclosure was deemed toincrease market response.